Exploring the impact of physiotherapy on health outcomes in older adults with chronic diseases: a cross-sectional analysis - Ravi Shankar Reddy; Khalid A. Alahmari; Mastour Saeed Alshahrani; Batool Abdulelah Alkhamis; Jaya Shanker Tedla; Mohammad A. ALMohiza; Basant Hamdy Elrefaey; Ghada M. Koura; Kumar Gular; Hani Hassan Alnakhli; Debjani Mukherjee; Vikram Sreenivasa Rao; et al. (Frontiers Media S.A., 2024)
ObjectiveThis study evaluates the impact of physiotherapy interventions on health outcomes and explores the correlation between physiotherapy session characteristics and improvements in health among older individuals.MethodsIn a cross-sectional design, 384 older adults with chronic conditions such as arthritis, osteoporosis, Chronic Obstructive Pulmonary Disease (COPD), diabetes, and hypertension were recruited.ResultsThe proportion of arthritis (39.1%) and hypertension (45.8%) was notably high. Participants receiving physiotherapy showed significant improvements in pain levels (mean reduction from 5.09 to 2.95), mobility scores (improvement from 3.0 to 3.96), and functional independence. A positive correlation was identified between the frequency of physiotherapy sessions and pain reduction (r = 0.26, p = 0.035), and a stronger correlation between session duration and both pain reduction (r = 0.38, p = 0.002) and mobility improvement (r = 0.43, p = 0.001). High satisfaction rates with physiotherapy were reported, and age was found to be a significant negative predictor of health outcomes (Coef. = −0.3402, p = 0.0009).ConclusionPhysiotherapy interventions significantly improve health outcomes in older adults with chronic diseases.